Automatic VMAT technique to treat glioblastoma: A two years' experience. (October 2021) - Arilli, C.; Zani, M.; Marrazzo, L.; Scoccianti, S.; Casati, M.; Compagnucci, A.; Talamonti, C.; Livi, L.; Pallotta, S.
Highlights: The planning process for VMAT irradiation of patients with glioblastoma is challenging due to the target proximity to critical organs. The use of the AutoPlanning module of Pinnacle3 improves the quality of VMAT irradiation for patients with glioblastoma. The success rate of the AutoPlanning module to plan patients with glioblastoma has been evaluated positively over two years. The use of the AutoPlanning positively impacts the operators workflow, greatly reducing planning time. Abstract: Purpose: The present work aims to guide the physicist in order to start automated planning for the VMAT treatment of glioblastoma multiforme (GBM) by giving a recipe that was set up and tested during a long-term (two years) evaluation. Methods: An automatic technique in AutoPlanning module of the Pinnacle3 (Philips Medical Systems, Fitchburg, WI) treatment planning system was created and validated by comparing dose distributions of automatic plans (APs) and manual plans (MPs) and by performing a blind AP-MP comparison on a cohort of 20 patients. Automatic technique was then applied to 145 patients and failures were recorded i.e. the number of times for which dose distributions produced by the automatic module were not suitable for treatment. Results: Each of the 20 APs considered in the validation step was clinically acceptable and proved to be better (15 cases) or equal (5 cases) respect to MPs. A statistically significant improvement in brain stem, optic pathways, cochleae, pituitary gland and scalp sparing was observed for APs, while no statistically significant differences were recorded in target coverage or plan parameters. For only 5 cases out of the 145 plans the operator intervention was needed in order to obtain a clinical acceptable plan, while for the remaining 140 plans the automatic created solution was suitable. Conclusions: A straightforward automatic procedure has been created and tested in our clinic. The AutoPlanning technique proposed represents a reliable tool to improve treatment planning efficiency and the recipe, here presented, could be simply imported to every radiotherapy center.